Research on the Metasurface for Single-Photon Avalanche Photodiode - Zhao, Tianqi; Chen, Linyao; Zhang, Sunhao; Ye, Yuyang; Liu, Chuang; Shi, Yan; Tian, Ying; Xu, Rui; Chen, Yi (Frontiers in Physics, 2020)
As the core device of quantum information field, single photon avalanche photodiode (SPAD) is a solid-state single photon detector with pico-second level time-resolution, low bias voltage, high signal-to-noise ratio and low cost. However, the photon detection efficiency (PDE) of SPAD is not ideal. Traditional method is to optimize the device structure, and the dark count or time resolution characteristics of the device might be sacrificed. The metasurface integrated on SPADs provides a novel approach to achieve higher PDE. As a result, the SPAD device structure could be independently designed to realize low dark count rate and good time resolution. In this paper, many kinds of metasurface structures that could enhance the incident photons absorption, are analyzed. Those structures compatible with CMOS or other easy to mass produce processes are attractive to be adopted to make revolutionary changes to conventional SPAD. As a results, the metasurface integrated SPAD would strongly push its applications in the quantum information, single photons imaging, life medicine, and other low level light detections.